Hepatitis B virus infection in undocumented immigrants and refugees in Southern Italy: demographic, virological, and clinical features. Issue 1 (December 2017) - Coppola, Nicola; Alessio, Loredana; Gualdieri, Luciano; Pisaturo, Mariantonietta; Sagnelli, Caterina; Minichini, Carmine; Di Caprio, Giovanni; Starace, Mario; Onorato, Lorenzo; Signoriello, Giuseppe; Macera, Margherita; Angelillo, Italo; et al.
Abstract Background The data on hepatitis b virus (HBV) infection in immigrants population are scanty. The porpoise of this study was to define the demographic, virological, and clinical characteristics of subjects infected with HBV chronic infection in a cohort of immigrants living in Naples, Italy. Methods A screening for HBV infection was offered to 1, 331 immigrants, of whom 1, 212 (91%) (831 undocumented immigrants and 381 refugees) accepted and were screened for hepatitis B surface antigen (HBsAg) and anti-hepatitis B core antibody (HBc). Those found to be HBsAg positive were further investigated at third-level infectious disease units. Results Of the 1, 212 immigrants screened, 116 (9.6%) were HBsAg positive, 490 (40.4%) were HBsAg negative/anti-HBc positive, and 606 (50%) were seronegative for both. Moreover, 21 (1.7%) were anti-human immunodeficiency virus positive and 45 (3.7%) were anti-hepatitis C virus positive. The logistic regression analysis showed that male sex (OR : 1.79; 95%CI : 1.28–2.51), Sub-Saharan African origin (OR : 6.18; 95%CI : 3.37–11.36), low level of schooling (OR : 0.96; 95%CI : 0.94–0.99), and minor parenteral risks for acquiring HBV infection (acupuncture, tattoo, piercing, or tribal practices, OR : 1.54; 95%CI : 1.1–2.16) were independently associated with ongoing or past HBV infection. Of the 116 HBsAg-positive immigrants, 90 (77.6%) completed their diagnostic itinerary at a third-level infectious disease unit: 29 (32.2%) were asymptomatic non-viremic HBsAg carriers, 43 (47.8%) were asymptomatic viremic carriers, 14 (15.6%) had chronic hepatitis, and four (4.4%) had liver cirrhosis, with superimposed hepatocellular carcinoma in two. Conclusions The data illustrate the demographic, clinical and virological characteristics of HBV infection in immigrants in Italy and indicate the need for Italian healthcare authorities to enhance their support for providing screening, HBV vaccination, treatment, and educational programs for this populations.